Aspecto da auditoria independente relacionados com informações e relatórios de sustentabilidade - Gruenfeld, Luís Carlos (2011)
The question of the enterprise sustainability started to be part of the reality of many companies in Brazil and abroad that had incorporated sustainability questions to their business plan. Ahead of this picture the present research searched to understand the sustainability questions and its impacts for the accountants and auditors, having as main focus to investigate if the practices adopted in Brazil for issuing sustainability reports and the auditors report are similar that adopted in Europe. For in such a way, a bibliographical research was carried through initially. Additionally, it was done a critical study of the Limited Report issued by the Independent Auditors of a large Brazilian Bank.. For a better understanding of the European and Brazilian reality two exploratory researches had been used. One issued by the Federation of European Experts (FEE) and an annual research issued by Guide of Examination on Sustainability matters. This research disclosed the existence of various questions that can be made with regard to the reports issued by independent auditors and can be object of future research. Also it was possible to verify that the reports issued by the auditors in Brazil are similar to the ones emitted in the Europe (limited scope), however in the Europe it has a very bigger number of companies that has its reports verified for independent auditors, specially small and medium business. In terms of disclosure, the research also showed some practices that can be considered for the Brazilian companies for improvement of its reports. Finally, new researches on the subject were suggested